Eco-theological Construction of Waste Management in the Rehobot Church Congregation, Kupang City, East Nusa Tenggara - Abdussamad, Zulkhaedir; Lestari Handayani, Suci (Sodality: Jurnal Sosiologi Pedesaan, 2022)
This study aims to analyze the social construction process of eco-theology-based waste management among the Rehobot church congregation in Kupang City, East Nusa Tenggara. This study uses the phenomenological method, especially Berger and Luckmann’s theory on the social construction of reality. The results of the study indicate that there is a relationship between waste management and the congregation’s beliefs, where the congregation interprets waste management activities as a form of obedience to God. As servants of Allah, humans must be able to overcome waste as one of the social problems of society, by turning waste into “bread”. Waste is seen as a challenge to human beings; if it can be managed wisely, it can be a blessing that is beneficial to life. Waste management activities in the congregation are the result of social construction that occurs through three dialectical phases. The externalization phase is marked by various products of waste management activities by the congregation, such as managing waste through waste banks, sorting waste, utilizing waste into compost, forming waste volunteers, and reducing the use of single-use plastic waste. The phase of objectivation occurs when the products of waste management activities that occur in the externalization phase undergo a reification process. The product of activity then undergoes institutionalization and is strengthened by the presence of religious legitimacy. The phase of internalization occurs when the procession of re-absorption of various waste management activity products of the congregations that have been objectivated, into the structures of subjective awareness.